Epidemiology and Haemato-Biochemical Changes in Mange Infested Camels - Pandya, Nidhi R; Mandali, Ghanshyam C; Dave, Keshank M; Raval , Sunant K (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Mange in camel, also named as sarcopticosis is defined as an extremely contagious skin disease characterized by scab formation, pruritic dermatitis, thickening and corrugation of skin and hair loss. A total of 21 positive cases of mange infestation were selected from those presented at the Veterinary Clinical Complex of the College, in Anand and from surrounding villages. The affected camels were divided into 3 groups, viz., B, C, D each group comprised of 7 camels, while seven healthy camels in group A served as control. The maximum prevalence of sarcoptic mange among infected animals was found in the age group of >6 years (52.38 %), followed by 4-6 years (38.09 %) and in <3 years age groups (9.52 %), and also in females than the males (85.71 vs 14.29%). The levels of haematological values, viz., haemoglobin, total erythrocytes count, packed cell volume, neutrophils, basophils, MCV and MCH were found to be significantly (p <0.05) decreased, whereas the total leukocytes count, lymphocytes and eosinophils were increased significantly (p <0.05) in mange affected camel as compared to healthy ones. The biochemical constituents, viz., total serum protein, alanine aminotransferase and zinc concentrations were found significantly (p <0.05) lower. In contrast, serum creatinine, aspartate aminotransferase and copper concentrations were increased significantly (p <0.05) in mange affected camels. The changes reflected that the mange infestation causes hepatocellular and renal damage, apart from general stress to the camel.